MORAL RIGHT IN ISLAMIC LAW - El_Haija, Mohammed I. Abu (European Scientific Journal, ESJ, 2015)
The issue of intellectual property rights concerns various aspects, as well as the generous (moral copyright) legal thoughts and legal regulations at the legislative situation within a short period of time. However, was this the right roots derived from the revealed legislation confiscation for centuries? Allah says in the Holy Qur’an: "Indeed, it is We who sent down the Qur’an and indeed, We will be its guardian” (Surat Al-Hijr verse 9). We should save Allah’s Qur’an from every twist and modification, and the Qur’an sources of Islamic law. This is because it is eternity at every time and place. However, we reassure those who are tempted to doubt the greatness of this religion and its universality by providing infallible proofs. The idea of this research is to establish the copyright moral rights in Islamic law, by taking the advantages and indications which is inspired by the Qur’an and the Sunna. Furthermore, we also considered sahaabah’s (Prophet Muhammad companion) unparalleled effort in checking hadiths science, the attributes of the Prophet, the greatest proof of coverage, and the immortality of this religion which is Allah.